2021
DOI: 10.51248/.v41i3.1197
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of Flacourtia jangomas (Lour.) Raeuschleaves and fruit methanolic extract on paracetamol-induced hepatotoxicity in HepG2 Cells

Abstract: Introduction and Aim: Plants have become the current focus of research in treating the various diseases and ailments. Flacourtia jangomas (Lour.) Raeusch belongs to the familySalicaceae. Itis a small deciduous fruit tree having immense nutritional and medicinal significance. Different parts of the plant are pharmaceutically used forcuring various ailments. In this study, we investigated the hepatoprotective activity of Flacourtia jangomas (Lour.) Raeusch leaves and fruit methanolic extract on Paracetamol induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…But, in this study the dose they have used is too high and it is not successful or rationale for human dose. 71…”
Section: Flacourtia Indicamentioning
confidence: 99%
“…But, in this study the dose they have used is too high and it is not successful or rationale for human dose. 71…”
Section: Flacourtia Indicamentioning
confidence: 99%
“…Both phytochemical and pharmacological studies have revealed that extracts from different parts and the main active components of F. jangomas demonstrate antimicrobial, antidiabetic, antidiarrheal, and antioxidant properties [20,21]. Moreover, a recent study noted the hepatoprotective activity of F. jangomas in the Paracetamol-induced HepG2 cell line [22].Hence, the objective of this research is to identify a highly selective compound that targets both the androgen receptor and/oracetyl cholinesterase, with the potential to serve as a therapeutic agent for the treatment of liver-related diseases.…”
Section: Introductionmentioning
confidence: 99%